PERLINDUNGAN HUKUM BAGI INVESTOR DALAM KEGIATAN PENANAMAN MODAL DI INDONESIA - Emiel Salim Siregar; Raudha Balqis; Fitria Rahmadani; Lulu Indah Eliyana; Dina Natasha Sayendra Putri; Adelia Fahriza Hasibuan (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to analyze the legal principles underlying investor protection, as well as the forms of preventive and repressive legal protection in investment activities in Indonesia. The research method used is normative legal research with a descriptive approach, through a literature review of relevant primary, secondary, and tertiary legal materials. The results indicate that investor protection is based on the principles of legal certainty, transparency, and equal treatment (non-discrimination), reinforced by the principles of national treatment and most favored nation. These principles play a crucial role in creating a fair, transparent, and legally certain investment climate. Furthermore, preventive legal protection is realized through clear regulations, information transparency, disclosure obligations by issuers, and oversight by relevant institutions to prevent violations. Meanwhile, repressive legal protection is provided through law enforcement mechanisms, sanctions, and dispute resolution for violations such as market manipulation and fraud. The conclusion of this study indicates that the combination of preventive and repressive protection forms a complementary system in ensuring investor security and confidence, thereby fostering a stable and sustainable investment climate in Indonesia.